Balance of payments constrained growth model: an examination of Thirlwall's Hypothesis using McCombie's Individual Country Method - Mat Ghani, Gairuzazmi (Taylor and Francis, 2006)
The balance of payments constrained growth (BOP) model is tested using the McCombie's cross-country and individual country test for 90 developed and developing countries for the period 1980 to 2000, and the McCombie's test is extended using export elasticity. If in the long run, the growth of exports is equal to the growth of imports and the affect of prices are not statistically significant, the estimated import elasticity from time series regression should not be statistically different from the BOP implied import elasticity, this also implied that the estimated export elasticity, also should not be statistically different from the BOP implied export elasticity. However, the finding shows that for only about 45% of the countries under study the individual country test is accepted even though cross-country analysis support the BOP model. Furthermore, for some countries where its estimated and implied import elasticity are not statistically different, its estimated and implied export elasticity are statistically different and vice-versa.